2020
DOI: 10.1186/s12916-020-01722-7
|View full text |Cite
|
Sign up to set email alerts
|

Arterial calcification at multiple sites: sex-specific cardiovascular risk profiles and mortality risk—the Rotterdam Study

Abstract: Background Evidence has pointed towards differences in the burden of arteriosclerosis according to its location and sex. Yet there is a scarcity of population-based data on aggregated sex-specific cardiovascular risk profiles, instead of single risk factors, and mortality risk according to the location of arteriosclerosis. We assessed sex-specific cardiovascular risk profiles and mortality risk associated with arteriosclerosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
(41 reference statements)
1
30
0
Order By: Relevance
“…This result was compatible with a previous report that the incidence of cerebral infarction was associated with calci cation of the thoracic aorta [10]. Moreover, a recent report showed that CVD risk pro les in both sexes that were differentially associated with calci cation at multiple vascular sites [11]. Although gender association was not clear in this study, this report supports the importance of assessing AAC, which is a potential risk factor for CVD.…”
Section: Discussionsupporting
confidence: 92%
“…This result was compatible with a previous report that the incidence of cerebral infarction was associated with calci cation of the thoracic aorta [10]. Moreover, a recent report showed that CVD risk pro les in both sexes that were differentially associated with calci cation at multiple vascular sites [11]. Although gender association was not clear in this study, this report supports the importance of assessing AAC, which is a potential risk factor for CVD.…”
Section: Discussionsupporting
confidence: 92%
“…In order to formally test for an interaction, we added an interaction term (on a multiplicative scale) between the (individual) APOE genotypes and the lifestyle factor to the cox proportional hazard model adjusted for the confounders. We acknowledge that lifestyle factors as well as the risk to develop CAD differs between men and women [27], and therefore we additionally stratified the analyses by sex.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Differing associations between calcification and cardiovascular disease risk depending on the vascular territory have been reported [33,34]. This is likely driven by differences in risk profiles for calcification at multiple sites [8]. The shift in current guidelines from coronary heart disease only towards a broader ASCVD outcome may require to consider assessment of calcification in other arteries than only the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence points towards a varying burden of calcification across various arteries [7,8], translating into differences in coronary heart disease and stroke risk depending on the proximity of the artery to the heart or brain [9,10]. The expanded focus of recent guidelines with the inclusion of stroke raises questions about the value of calcification assessment in other vascular territories for ASCVD risk prediction and stratification, beyond sole assessment of CAC.…”
Section: Introductionmentioning
confidence: 99%